Salacia fugax, an elusive new South American Salacioideae (Celastraceae) (2017)
A new South American species of Salacia (Celastraceae, Salacioideae) found in Colombia and Venezuela, Salacia fugax Lombardi & M.Serna is described here. It is characterized by its indument, small long acuminate leaves with short petioles, branched inflorescences, flowers with an annular-pulvinate disk, and small pyriform fruits. This new species resembles S. mennegana J.Hedin ex Lombardi and S. opacifolia (J.F.Macbr.) A.C.Sm. by its short petioles, leaf shape, slender branched inflorescence, perianth form, and similar disc, but S. fugax differs by its hairs, leaf size and apex, calyx, and fruit size and shape.